Analisis Produk dan Pelayanan Syariah terhadap Minat Menabung Masyarakat Muara Tembesi (Studi Kasus BSI Cabang Muara Bulian) - Sumantri Sumantri (CITRA EKONOMI, 2022)
This research is related to the fields of Islamic banking science. In connection with the approaches taken in the theories related to products, services and interest in saving. This research is a descriptive quantitative research with data sources, namely primary data. Data collection techniques using interviews and questionnaires with a sample of 95 people. Data analysis used validity test, reliability test, multiple linear analysis, t test, and F tes.The results of the research with the SPSS program obtained partial measurement results (t test) the product variable has an influence on interest in saving with a value of tcount 6,011> ttable1,985. The results of the partial measurement (t test) of the service variable have an influence on interest in saving with a value of tcount 5,458> ttable1,985. Simultaneous research results (F test) show that product and service variables have an influence on interest in saving forIndonesian